Optimization of The Oxy-Acetyline Gas Cutting Process on Aisi 1045 Steel Material to Produce Minimum Width Kerf - Mohammad Egie Syahputra; Haipan Salam; Asep Hadian Sasmita (Universitas Pendidikan Indonesia (UPI), 2021)
This research is intended to determine the optimum combination of parameters and how much the contribution of the parameters of cutting speed, oxygen gas pressure, and nozzle distance to the width of the cutting kerf. This research was conducted with a method, namely Taguchi Design of Experiments (DoEs) by varying the process factors used in the AISI 1045 steel material cutting process. The control factors in this study consisted of three factors, namely cutting speed, gas pressure, and tip distance. The cutting speed and cutting gas pressure are significant factors in the optimization of the AISI 1045 steel cutting process for minimum kerf width with a contribution of 95.6%, while the tip / nozzle height factor is not significant in the optimization of the AISI 1045 steel cutting process for the kerf width minimum. The optimum parameter values to obtain the minimum kerf width in AISI 1045 steel are cutting speed of 250 mm/min, gas pressure of 3 kgf/cm2, and tip height of 4 mm. Furthermore, the results of the verification tests carried out indicated that the optimal process parameter formula obtained is feasible to use, indicated by the S / N ratio and confidence interval (CI) of prediction and verification that coincide with one another. The optimal process parameter formula can be used as a reference for industrial production activities with a 95% success rate.